2019
DOI: 10.1016/j.scitotenv.2019.06.534
|View full text |Cite
|
Sign up to set email alerts
|

Use of fish otoliths as a temporal biomarker of field uranium exposure

Abstract: This study aimed to determine uranium (U) pollution over time using otoliths as a marker of fish U contamination. Experiments were performed in field contamination (~20 μg L−1: encaged fish: 15d, 50d and collected wild fish) and in laboratory exposure conditions (20 and 250 μg L−1, 20d). We reported the U seasonal concentrations in field waterborne exposed roach fish (Rutilus rutilus), in organs and otoliths. Otoliths were analyzed by ICPMS and LA-ICP SF MS of the entire growth zone. Concentrations were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Aquatic ecosystems are increasingly threatened by human-mediated sources of contaminants (Guédron & Acha 2021;Schwarzenbach et al 2006). Elevated levels of metal contaminants have been measured in archival tissues such as otoliths, fin rays, and eye lenses, to monitor elevated exposures and corroborate water quality concerns (e.g., Dove & Kingsford 1998;Mounicou et al 2019;Selleslagh et al 2016;Sun et al 2019). Contaminants such as selenium have also been measured in otoliths from several species and systems to evaluate increased exposure.…”
Section: Contaminantsmentioning
confidence: 99%
“…Aquatic ecosystems are increasingly threatened by human-mediated sources of contaminants (Guédron & Acha 2021;Schwarzenbach et al 2006). Elevated levels of metal contaminants have been measured in archival tissues such as otoliths, fin rays, and eye lenses, to monitor elevated exposures and corroborate water quality concerns (e.g., Dove & Kingsford 1998;Mounicou et al 2019;Selleslagh et al 2016;Sun et al 2019). Contaminants such as selenium have also been measured in otoliths from several species and systems to evaluate increased exposure.…”
Section: Contaminantsmentioning
confidence: 99%
“…We previously conducted a comparative study on element composition profiles of Na, Mn, Fe, Ni, Cu, Sr, Ba, and Ca in otolith cores of C. nasus from the Yangtze River, Yellow Sea, and Poyang Lake using LA-ICPMS analysis. The results of the study suggested a natal homing capability of this species; the Poyang Lake, Yangtze River, and Yellow Sea seemed to be the natal lake, migration pathway, and feeding ground, respectively, for this species [ 48 ]. As indicated by Arostegui and Quinn [ 65 ], based on studies of salmonid fish of the North American, Asian, European, and African ranges, lakes provide spawning, rearing, and refuge habitats and support life-history variants, reproductive ecotypes, and trophic morphs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, otoliths are acellular and metabolically inert [ 45 , 46 ] and are not resorbed or otherwise chemically altered via biogenic processes. Consequently, otolith microchemistry provides reasonable timeline representations of the chemical composition of the waters in which fish live during the course of their lives [ 47 , 48 ]. Otoliths have previously been used to determine fish natal habitats, population connectivity, and distribution areas [ 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other targeted structures to reveal past element exposure events include bones and otoliths. Fish otoliths are stable and durable structures that serve as a temporal biomarker for environmental monitoring and investigation of migration patterns. ,, Ishii et al analyzed bones of lead-exposed birds to measure the lifetime exposure of Pb. Bones had up to 90% of the Pb burden (approximately 90%) and were correlated to levels in other soft tissues.…”
Section: Applicationsmentioning
confidence: 99%